Public Interest Standing and Judicial Review of Environmental Matters: A Comparative Approach - Hammons, Jeffrey T. (Columbia Journal of Environmental Law, 2019)
Judicial review is vital to clarifying and enforcing environmental laws in the United States. The public can use judicial review to protect the environment and hold the government accountable for environmental harms. Redressing environmental harm is often led by non-governmental organizations (“NGOs”) specializing in environmental issues. However, the modern standing doctrine can be a barrier to redressing environmental harms because it is not flexible enough to address the unique factual situations that arise in environmental litigation. One situation that current standing doctrine struggles to address is when government action affects the public generally, but no individual person is harmed in a specific manner. That scenario can occur, for example, when the government fails to address a pollutant known to be harmful due to its climate change implications, as addressed in Massachusetts v. EPA. Another frequent situation is when government action affects a particular environment, but no individual has a sufficient direct interest in that environment to satisfy the current standing doctrine’s injury-in-fact or redressability requirements. For instance, when the government grants mineral leases in uninhabited locations such as the Arctic National Wildlife Refuge, often no individual other than the lessee has a sufficient interest. This Note has two goals. First, the Note provides the reader with an understanding of the extant public interest standing doctrine in England, Canada, and Australia (the “Commonwealth countries”). Next, by utilizing the lessons gleaned from Commonwealth countries’ experiences, this Note advocates that the United States should adopt discretionary public interest standing modeled after the kind that exists in the Commonwealth countries. The Commonwealth countries created public interest standing for judicial review as a complement to their traditional private-rights model of standing, which had existed for centuries before the creation of the modern administrative state.3 In those countries, public interest standing is only granted in judicial review actions that are brought by plaintiffs who have a genuine interest in the subject matter even if they lack a direct interest necessary under traditional doctrines of standing. The doctrine is also dynamic: public interest standing may be granted based upon the pleadings and then later denied if evidence at trial does not support the initial standing. The public interest standing model adopted by the Commonwealth countries is compared against the U.S. model for four reasons. First, the model in Commonwealth countries was created by their judiciaries; just as in the United States, the judiciary is the sole arbiter of standing doctrine. Second, both the United States and the Commonwealth countries are common law countries and therefore share a legal tradition. This shared tradition is helpful because it means the various judiciaries approach legal questions similarly. Third, the countries have analogous administrative structures and statutory judicial review provisions, and these similarities allow comparative analyses to focus on more nuanced details. Fourth, each country has similar separation of powers doctrines, and this commonality is important due to the role separation of powers doctrine plays when issues of standing arise. In the United States, there are several arguments against expanded standing; however, the Commonwealth countries faced and overcame similar arguments. Some of these arguments are: (1) liberal standing would distract from the business of governing; (2) liberal standing would increase financial costs and further burden the judicial system; (3) liberal standing would increase the number of judicial review petitions, and thus would increase delay in already overburdened courts;7 and (4) courts are not the place for citizens to air their intellectual or emotional grievances, however strongly held.8 Part II reviews the public interest standing doctrine’s evolution in the United States and the Commonwealth countries. Part III addresses the above arguments against liberal standing, utilizing lessons from the Commonwealth countries. Part IV concludes, arguing for liberalization of standing in the United States. Before addressing the above arguments and utilizing lessons from the Commonwealth countries, an overview of the standing doctrine’s evolution in each country is necessary.